Penerapan Etika dalam Kepemimpinan serta Kepemimpinan Transformasional terhadap Kinerja Pegawai (Studi Literatur) - Danang Nugroho; Qoriatul Azizah Nurfalah; Sani Agisni; Sinta Novita; Siti Mulyani; Syahrul Ghupron Mubarok (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The implementation of ethical leadership and transformational leadership has become a major focus in modern management literature. This literature study analyzes the concepts, characteristics, and impacts of both types of leadership in an organizational context. Leadership ethics emphasize the importance of integrity, honesty, and social responsibility in decision making and interactions with subordinates. On the other hand, transformational leadership involves inspiring, visioning, motivating, and developing subordinates to achieve common goals. Literature analysis shows that the implementation of ethical leadership can increase trust, loyalty and organizational performance, while transformational leadership is associated with innovation, adaptation and competitive advantage. This study also highlights the importance of integration between these two approaches to create an ethical and highly competitive work environment.